1996
DOI: 10.1016/0042-6989(95)00191-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the compensatory responses to positive and negative lenses of intermittent lens wear and ciliary nerve section in chicks

Abstract: This study examined the ocular compensation to lens-induced defocus in chick and the effect of interrupting lens wear on a daily basis. Eyes fitted with +10 D lenses at hatching compensated rapidly, with almost complete compensation after 4 days of lens wear; they had decreased vitreous chamber depth compared to normal eyes and were thus hyperopic when the lenses were removed. In contrast, adaptation to the -10 D lenses was much slower, was still incomplete after 9 days of lens wear, and in this case, eyes had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
160
5
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 25 publications
13
160
5
1
Order By: Relevance
“…Conversely, an insufficient axial growth will place the focal plane of the eye behind the retina: the eye is hyperopic or far-sighted (1). Studies on experimental animal models have demonstrated that emmetropization is driven by visual inputs (2, 3, and 4) and primarily controlled by the retina (2,4). The control of ocular axial growth by visual factors has been extensively investigated in chicken experimental models (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, an insufficient axial growth will place the focal plane of the eye behind the retina: the eye is hyperopic or far-sighted (1). Studies on experimental animal models have demonstrated that emmetropization is driven by visual inputs (2, 3, and 4) and primarily controlled by the retina (2,4). The control of ocular axial growth by visual factors has been extensively investigated in chicken experimental models (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on experimental animal models have demonstrated that emmetropization is driven by visual inputs (2, 3, and 4) and primarily controlled by the retina (2,4). The control of ocular axial growth by visual factors has been extensively investigated in chicken experimental models (3,4). Applying negative lenses over the eye of the chicken places the focal plane behind the retina (hyperopic defocus), accelerates axial eye growth and leads to a myopic condition (Lens Induced Myopia, LIM).…”
Section: Introductionmentioning
confidence: 99%
“…However, several animal studies that blocked accommodation in eyes exhibiting active growth (Schaeffel et al, 1990;Schwahn & Schaeffel, 1994;Schmid & Wildsoet, 1996), Chapter 1: Literature review 5 concluded that accommodation is not essential for either natural emmetropization or emmetropization in response to imposed defocus to occur.…”
Section: Form-deprivation: 113mentioning
confidence: 99%
“…For example, Schmid and Wildsoet (1996) found that chicks wearing high positive powered lens developed hyperopia, and a short period of normal vision intervention helped to prevent myopia development. Chick model also showed that the defocus induced by negative and positive lenses can be compensated, implying the absence of accommodation cues does not impede the blur signal being recognised by retina (Diether & Schaeffel, 1997).…”
Section: Myopia In Animalsmentioning
confidence: 99%
“…The development of refraction in the models of monkey (Hung et al, 1995) and tree shrew (McBrien et al, 1999), can be altered by wearing by positive or negative lenses. Animal models have shown that the development of refraction and axial length during early life can be manipulated by lens wear: a hyperopic defocused image forms behind the retina (using negative lens) causes axial elongation and myopic shift in refraction, whereas a myopic defocused image forms in front of the retina (using positive lens) develops hyperopia (Edwards, 1996;Schmid & Wildsoet, 1996).…”
Section: Myopia In Animalsmentioning
confidence: 99%